2007
DOI: 10.1107/s1600536807000906
|View full text |Cite
|
Sign up to set email alerts
|

3-(3-Bromophenyl)-1-(2-naphthyl)prop-2-en-1-one

Abstract: Key indicatorsSingle-crystal X-ray study T = 100 K Mean (C-C) = 0.002 Å R factor = 0.035 wR factor = 0.096 Data-to-parameter ratio = 32.7For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Molecules that possess such a system have relatively low redox potentials and have a greater probability of undergoing electron-transfer reactions. Crystal structures have been reported for 3-(3-bromophenyl)-1-(4-bromophenyl)prop-2-en-1-one (Teh et al, 2006), 3-(3bromophenyl)-1-(2-naphthyl)prop-2-en-1-one (Moorthi et al, 2007), (E)-1-(3-bromophenyl)-3-(4-ethoxyphenyl)prop-2-en-1-one (Fun et al, 2008), (E)-3-(biphenyl-4-yl)-1-(3-bromophenyl)prop-2-en-1-one (Dutkiewicz et al, 2009), (2E)-1-(3-bromophenyl)-3-(6-methoxy-2-naphthyl)prop-2-en-1-one (Harrison et al, 2010), (2E)-1-(3-bromophenyl)-3-(4,5dimethoxy-2-nitrophenyl)prop-2-en-1-one (Jasinski et al, 2010), (E)-1-(3-bromophenyl)-3-(3,4-dimethoxyphenyl)prop-2-en-1-one (Escobar et al, 2012), (E)-1-(3-bromophenyl)-3-(4nitrophenyl)prop-2-en-1-one (Harini et al, 2017) and (E)-1-(3-bromophenyl)-3-(3-fluorophenyl)prop-2-en-1-one (Rajendraprasad et al, 2017). We herewith report the crystal and molecular structure of the title compound.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Molecules that possess such a system have relatively low redox potentials and have a greater probability of undergoing electron-transfer reactions. Crystal structures have been reported for 3-(3-bromophenyl)-1-(4-bromophenyl)prop-2-en-1-one (Teh et al, 2006), 3-(3bromophenyl)-1-(2-naphthyl)prop-2-en-1-one (Moorthi et al, 2007), (E)-1-(3-bromophenyl)-3-(4-ethoxyphenyl)prop-2-en-1-one (Fun et al, 2008), (E)-3-(biphenyl-4-yl)-1-(3-bromophenyl)prop-2-en-1-one (Dutkiewicz et al, 2009), (2E)-1-(3-bromophenyl)-3-(6-methoxy-2-naphthyl)prop-2-en-1-one (Harrison et al, 2010), (2E)-1-(3-bromophenyl)-3-(4,5dimethoxy-2-nitrophenyl)prop-2-en-1-one (Jasinski et al, 2010), (E)-1-(3-bromophenyl)-3-(3,4-dimethoxyphenyl)prop-2-en-1-one (Escobar et al, 2012), (E)-1-(3-bromophenyl)-3-(4nitrophenyl)prop-2-en-1-one (Harini et al, 2017) and (E)-1-(3-bromophenyl)-3-(3-fluorophenyl)prop-2-en-1-one (Rajendraprasad et al, 2017). We herewith report the crystal and molecular structure of the title compound.…”
Section: Chemical Contextmentioning
confidence: 99%
“…For applications of chalcones, see: Cho et al (1996); Dinkova-Kostova et al, (1998); Fichou et al (1988); Liu et al (2003); Nielson et al (1998); Rajas et al (2002); Sarojini et al (2006). For related structures, see: Fischer et al (2007a,b,c); Moorthi et al (2007); Sarojini et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…P1, with fairly similar reduced cell repeat vectors, in (II), the inter-axial angles are all greater than 90 , whereas those in (IV) are all less than 90 , so that these compounds cannot be even approximately isostructural. The supramolecular assembly of (IV) was described (Moorthi et al, 2007) as comprising chains built from C-HÁ Á ÁBr hydrogen bonds. However, this description must be questioned on two grounds; firstly, the HÁ Á ÁBr distance in question, 2.93 Å , is not significantly shorter than the sum, 2.94 Å , of the van der Waals radii (Rowland & Taylor, 1996), and secondly, it has been convincingly demonstrated that Br atoms bonded to C atoms are extremely poor acceptors even from good hydrogen-bond donors, such as O-H and N-H, and correspondingly worse from a weak donor, such as C-H (Brammer et al, 2001;Thallapally & Nangia, 2001).…”
Section: Br34mentioning
confidence: 99%
“…3-(3-Bromophenyl)-1-(naphthalen-2-yl)prop-2-en-1-one, (IV) (Scheme 2) (Moorthi et al, 2007), is a positional isomer of compound (II), differing from it only in the location of the Br substituent. While compounds (II) and (IV) crystallize in the same space group, i.e.…”
Section: Br34mentioning
confidence: 99%